Control of the structural condition and abrasive wear resistance of weld metal by alloying. - Куликовский, Р.А.; Холод, А.В.; Капустян, А.Е.; Осипов, М.Ю.; Андрущенко, М.И. (Problems of Tribology, 2015)
Kulikovsky R.A., Holod A.V., Kapustyan A.Е., Osіpov M.Y., Andrushchenko M.І. Control of the structural condition and abrasive wear resistance of weld metal by alloying.It was shown that the ability to self-strengthening high surface friction and abrasion resistance of high-carbon steels Fe-C-Cr with many metastable retained austenite obtained by hardening can not be realized if the structure is formed under conditions of uncontrolled thermal cycle of welding, in particular for restoring the dies molds for pressing refractory and building products. This is due to the lack of stability of austenite to pearlite and intermediate transformations in these condi-tions the cooling weld metal. Solution to this problem through the use of forced cooling weld metal using a water-cooled copper mold dies for complex structures is almost impossible.The possibility of providing the necessary structures in the deposited layer by further doping. The search was con-ducted among alloys temperature martensite start Mn which is in the range of -20° C - + 20° C or slightly deviates from this range. To simplify the procedure and reduce the complexity of choosing alloys meet this condition are summarized known analytical and graphics depending on the chemical composition of the MN in the systems Fe-C, Fe-C-Cr, Fe-C-Mn, Fe-C-Mn-Cr and the obtained expression relating a carbon content in the alloys meets the requirements of - MH  20 ° C with a concentration of chromium and manganese in the range: C - 0.6 ... 2%; Cr - 0 ... 12%; Mn - 0 ... 8.8%.It is established that ensuring sufficient stability of the austenite to decay under cooling conditions of uncontrolled thermal deposition cycle (without forced heat removal) can be achieved by further doping of high-chromium alloys of man-ganese, while reducing the carbon content in amounts proportional influence of these elements on the martensite start tem-perature.It is shown that the greatest ability to hardening and wear resistance in chromium-manganese alloys with the struc-ture of the weld metal formed without forced cooling is achieved in surfacing alloy type 120Х4Г2.